Implementation of the Picture Word Inductive Model (PWIM) Assisted by a Digital Dictionary in Teaching Arabic Writing Skills - Sulthan Zainul Amin; Shofwan Sholahudin; Asep Sopian (Didaktika: Jurnal Kependidikan, 2025)
This study explores the integration of the Picture Word Inductive Model (PWIM) with the use of digital dictionaries in teaching Arabic writing skills. Employing the Integrative Literature Review (ILR) approach, the study analyzes literature related to PWIM, digital dictionary technology, and the teaching of Arabic writing skills. The findings indicate that PWIM is effective in enhancing vocabulary acquisition, grammar, and sentence structure through a visual and systematic approach. Digital dictionaries complement this method by providing quick access to vocabulary, contextual meanings, and word usage variations. The resulting teaching model involves structured steps, starting from image-based vocabulary introduction to the gradual development of complete texts. The implementation model of PWIM assisted by a digital dictionary has significant implications for Arabic language learning. For teachers, this method helps optimize image-based and inductive learning while guiding students in using digital dictionaries to select the appropriate vocabulary in writing contexts. For educational institutions, this study highlights the importance of strengthening digital literacy through teacher training and the integration of technology into the curriculum. For researchers, these findings open opportunities to explore the effectiveness of this method through empirical studies at various educational levels and compare it with other approaches in teaching writing skills. This research is expected to serve as a reference for educators, institutions, and educational technology developers in creating more effective, innovative, and engaging Arabic language learning experiences.